2019
DOI: 10.7748/mhp.2019.e1304
|View full text |Cite
|
Sign up to set email alerts
|

Implementing co-production in traditional statutory mental health services

Abstract: Since the publication of A Vision for Change (Department of Health and Children 2006), which sets out the direction for mental health services in Ireland, new approaches to interacting with people who have lived experience of mental ill health have emerged. Co-production is one such approach. Co-production is a word used to describe the creation of a dialogical space where the service user, family members, carers and service providers enter a collaborative medical partnership to improve their own care and also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…For instance, creating an environment that allows individuals to discuss and work through past traumas without dismissing them is vital to the co-productive work in CAMHS. This need for a suitable environment is in line with previous literature, such as Norton [18], who suggests the need for "a dialogical space" for true "collaboration" to occur [18]. Additional to this, the review identified six key principles that are fundamental to such collaborations.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…For instance, creating an environment that allows individuals to discuss and work through past traumas without dismissing them is vital to the co-productive work in CAMHS. This need for a suitable environment is in line with previous literature, such as Norton [18], who suggests the need for "a dialogical space" for true "collaboration" to occur [18]. Additional to this, the review identified six key principles that are fundamental to such collaborations.…”
Section: Discussionsupporting
confidence: 72%
“…Additional to this, the review identified six key principles that are fundamental to such collaborations. These principles support services in the redistribution of power so that both the user and provider are equal within the "dialogical space" [18,40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the positive appraisal of the facilitator training, both clinical and peer facilitators noted challenges in developing genuinely equitable partnerships in practice, revealing that at times they slipped back into their traditional hierarchical roles of 'patient' and 'provider'. Given that the implementation of co-production is in its infancy in mental health services [63][64][65][66], this is not a surprising nding and highlights the importance of support during intervention implementation (in the form of informal mentoring or clinical supervision), as well as endorsement by service leaders and senior managers. In the context of coproduction, the availability of a streamlined and hassle-free payment system for peers is of critical importance.…”
Section: Discussionmentioning
confidence: 99%